Research performance and knowledge mapping of King Fahd University of Petroleum and Minerals, Dhahran, Saudi Arabia: A bibliometric analysis of literature indexed in Web of Science (2011-2020) - Rahaman, Md Safiqur; Baquer, Minhajuddin Mohammed; Al-Baridi, Dr. Saleh A.; Ansari, Khadeeja M N (Qualitative and Quantitative Methods in Libraries; Vol 10 No 4 (2021): December issue 2021, 2022)
Purpose: King Fahd University of petroleum and minerals is one of the best universities in Saudi Arabia and the Gulf region. The primary goal of this study is to analyze research output and mapping knowledge of King Fahd University of petroleum and minerals, Dhahran, Saudi Arabia, between 2011 and 2020. Methodology: The present study employed the bibliometric method to explore the research performance of the King Fahd University Petroleum and Minerals between 2011 and 2020. The study focused on bibliometric parameters such as annual research growth and its citation impact over the years, the prolific researcher, authorship pattern, relevant sources, subjects-wise research and level of collaborations by authors and countries, etc. Results: The results show that out of 12494 papers, the highest research was 928 papers published in 2020. The majority of the 9906 publications were published as journal articles, and the “ Arabian Journal for Science and Engineering” ranked first with 256 articles. B.S. Yilbas identified the most prolific author with 342 papers, and the three authorship (3509) papers were the most preferred authorship pattern. Moreover, the subject ‘Engineering’ has the highest number of published papers. Furthermore, the most commonly used author’s keywords are adsorption, Corrosion, Laser, Laser, Solar, corrosion inhibition, and nanoparticles between 2011 and 2020. The results also show Saudi Arabia vs. the United States was most the collaborative country for KFUPM research with 1365 publications, followed by Pakistan and India, and the collaboration index noted as 1.42. The study also recommends some valuable suggestions to accelerate and produce more research in KFUPM.